EFEKTIFITAS RELAKSASI BENSON TERHADAP TEKANAN DARAH DEWASAHIPERTENSI DI WILAYAH KERJA PUSKESMAS KURANJI - Khairul Andri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Hypertension is a disease that interventions addressed to mantain blood pressure within normal limits are needed. The purpose of this study was to investigate the effectiveness of Benson's relaxation on blood pressure in hypertensive adults. The study was quasi-experimental with one group pretest-posttest design, The study involved 10 hypertensive adults in RW 16 Korong Gadang Village from January to August 2021. The results showed that the average blood pressure of hypertensive adults before the intervention was 152.00 mmHg for systolic and 98.00 mmHg for diastolic, and after the intervention was 134.50 mmHg for systolic and 92.00 mmHg for diastolic pressure, where standard deviation of systolic pressure was 7.619 and diastolic pressure was 4.216. Bivariate analysis using dependent t-test revealed p-value = 0.000, indicated that Benson relaxation therapy was effective in reducing blood pressure in hypertensive adults. It is recommended to employ regular Benson relaxation technique in order to maintanin blood pressure within normal limits in hypertensive adults, and family involvement plays an important role in the process.